การเพิ่มค่าความร้อนของเชื้อเพลิงอัดเม็ดจากทางใบและเปลือกนอกต้นปาล์มน้ำมัน - กฤติย์ภรณ์ ตรังคประสิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The heating value enhancement of fuel pellet from frond and trunk of oil palm was studied here. Waste glycerol, glue, spent wash liquor, and glycerol residue were used as adhesive. The aim was to find the optimum ratio of raw material by using the suitable adhesive. Raw material ratios were varied of 4 values from 50 to 80%, water ratios were varied of 3 values from 0 to 10%, and waste glycerol ratios were varied for 7 values from 20 to 50%. Adhesive variation in fuel pellet production from oil palm frond was produced by ratio, frond to water to waste glycerol : 70-0-30. The results showed that ratio of pelletized fuel from frond mixed with waste glycerol gave the highest heating value equal to 19.22 MJ/kg. While the pellet of frond with other adhesives offered heating value of 16.23–16.39 MJ/kg which was lower than the pellet standard (>17 MJ/kg). Such, waste glycerol was chosen as a suitable adhesive for varying ratio of mixture which was the next step. The optimum ratio of frond to water to waste glycerol was the quantity of wasteglycerol 30% which gave heating value of 19.22-19.30 MJ/kg, pelletizing ratio of 91.84-94.71%, specific density of 996.01-996.35 kg/m3, moisture content of 2.12-3.13%, volatile matter of 82.01-83.11%, fix carbon content of 1.09-2.31%, and ash content of 12.46-13.58%. The optimum ratio of trunk to water to wasteglycerol was the quantity of wasteglycerol 20-30% which gave heating value 19.02-19.80 MJ/kg, pelletizing ratio of 80.19-84.13%, specific density of 894.74-941.33 kg/m³, moisture content of 3.39-6.32%, volatile matter of 75.88-81.80%, fixed carbon content of 4.66-8.82% and ash content of 8.97-10.14% which ash content of frond and trunk were higher than the standard. Results showed that the mixing of fuel pellets from frond and trunk of oil palm with waste glycerol was suitable for use as fuel which was an alternative for industries.